The Influence of Planning and Volition on E-Learning Utilization During Technology Transitions - Christian Seiberling; Simone Kauffeld (International Journal of Training and Development, 2025)
The purpose of this study was to identify factors linked with e-learning utilization. This empirical study ( N 0.167em=0.167em381) was conducted in partnership with a German bank and measured e-learning utilization as the degree to which participants thoroughly completed an extensive number of automatically provided e-learning courses on new banking software. The results suggest that e-learning utilization is influenced by the workplace context in which e-learning takes place (supervisor support, personal capacity for learning), the planning of the learning process, and a learner's volition to learn. Planning the e-learning process mitigated an unfavourable learning environment in terms of limited time resources for learning to some extent.
Keywords: 650; e-learning; motivation to learn; personal capacity for learning; planning to learn; supervisor support; volition to learn